2019
DOI: 10.1111/jpc.14658
|View full text |Cite
|
Sign up to set email alerts
|

Use of clinician‐performed ultrasound in the assessment of safe umbilical venous catheter tip placement

Abstract: Aim Safe tip placement of umbilical venous catheters (UVCs) in sick neonates is critical in minimising risk. We aimed to demonstrate the utility of clinician‐performed ultrasound (CPU) in identifying UVCs that are placed within small intrahepatic portal vessels or within the heart despite the appearance of being well placed on X‐ray. Methods This was a retrospective observational study of preterm and term neonates who had a UVC placed and the position assessed by X‐ray and/or CPU according to the Royal Prince … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Median (IQR) birth weights were 1,672 (1,060-2,365) and 1,445 g (1,020-2,245) in USG and blind groups, respectively. The age of neonate (median [IQR]) at the insertion of the umbilical line was 5 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) hours in the USG group and 2 (2-12) hours in the blind group. The remaining baseline characteristics were comparable in both groups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median (IQR) birth weights were 1,672 (1,060-2,365) and 1,445 g (1,020-2,245) in USG and blind groups, respectively. The age of neonate (median [IQR]) at the insertion of the umbilical line was 5 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) hours in the USG group and 2 (2-12) hours in the blind group. The remaining baseline characteristics were comparable in both groups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Limited studies are available using USG to confirm the correct position of the UVC in neonates [7,8,[10][11][12][13][14][15][16]. Most studies except one [16] are observational studies with a small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…In the lateral view, it can be suitably visualized [30]. Some authors advocate bedside US, which is convenient, non-invasive, and radiation-free and allows real-time guidance of UVC [31][32][33], as the gold standard for verification of the position of the UVC [34,35]. Moreover, Lafortune reported that the DV was visible upon US in the first hours after birth as a small vein coursing posteriorly and cephalically from the umbilical portion of the left PV [36].…”
Section: Estimated Uvc Insertional Length For the Present Case (Cm)mentioning
confidence: 99%
“…Point-of-care ultrasound (POCUS) is a convenient, non-invasive modality that does not require radiation exposure. It can guide UVC in real time and monitor the catheter tip position ( 5 ). Early detection of catheter tip displacement can effectively prevent arrhythmia, pericardial effusion ( 6 ), pericardial tamponade ( 7 ), endocarditis, pleural effusion ( 8 ), liver hemorrhage, liver tissue necrosis ( 9 ), and other serious complications.…”
Section: Introductionmentioning
confidence: 99%